Calcium carbonate scaling and seeding induced precipitation in FO treating textile reverse osmosis concentrate. (December 2022) - Cui, Ming-Qi; Dong, Xiang-Yu; Wang, Jian-Xiao; Hu, Yun-Xia; Xu, Xin-Hua; Cheng, Li-Hua
Abstract: Forward osmosis (FO) technology has been applied in the treatment and reclamation water from reverse osmosis concentrate. The performance of treating simulated textile reverse osmosis (sROC) was investigated with a focus upon the effect of calcium carbonate scaling and seeding induced precipitation on flux behavior. The effects of DS dilution & reverse salt flux (α), FS concentration & concentration polarization (β) and carbonate calcium scaling (γ) on flux decline were quantified based on the same water recovery at different DS (NaCl) concentration and FS salinity. The calcium carbonate scaling was found to contribute more to the flux decline when the FS salinity was 5000 ± 500 mg/L TDS at higher DS concentration. When the salinity of FS was increased to 10, 000 ± 500 and 15, 000 ± 500 mg/L TDS, the water flux was found higher under the situation of scaling than those of no scaling due to the fact that CaCO3 precipitation could inhibit the increase of osmosis pressure in FS in some degree. CaCO3 seeding induced precipitation in FO process promoted water flux and thus alleviated the calcium carbonate scaling on FO membrane. This work proposed a new view on the membrane scaling in FO process treating feed solution like reverse osmosis concentrate (ROC), and the seeding induced precipitation turned out to be an efficient strategy to alleviate calcium scaling in FO process and improve performance. Graphical abstract: Unlabelled Image Highlights: The effects of DS dilution and RSF, FS concentration, CP and membrane scaling on FO flux decline were quantified. The concentration of feed solution other than calcium carbonate scaling dominated flux decline in FO treating ROC. Calcium carbonate scaling was found to alleviate the flux decline other than aggravate FO flux decline when treating ROC. CaCO3 seeding induced precipitation in feed solution could alleviate the membrane scaling and improve FO performance.